(untitled) (Research, Society and Development, 2023)
Occupying prominent positions in mortality and morbidity rates, cancer has become one of the main pathologies that public health has dealt with in the last 5 years due to the increase in cases. In this context, breast cancer stands out for being the second most frequent type in the world, for not having a single cause but rather the possibility of the interconnection of several factors, some women only discover the diagnosis late, when the degree is already high. high. Using the narrative bibliographic review methodology, the objective of this article is to expose the impacts of treatment on the self-esteem and self-image of women with breast cancer, thus highlighting the psychological, physical and social results derived from this disease. Considering the impacts exposed in the results, follow-up with a multidisciplinary team is seen as necessary, as well as the importance of Psychology during treatment for the acceptance of the “new body” and “new life”.